Neanderthals in Italy: an evaluative review of current archeological knowledge - Skeates, Robin (Journal of Mediterranean Earth Sciences, 2023)
This paper briefly reviews current archeological knowledge of Neanderthals in Italy. It is written from the perspective of an international consumer - critical and constructively provocative - of Italian archeological data. It considers eight themes: origins; paleoclimate and ecological refugia; competition between predators; seasonal mobility and dwelling; resource exploitation; intercommunicating; behavioural changes; Anatomically Modern Humans. It then highlights five areas for further research: dating; open sites; plants; human remains; behavioral changes during MIS 3.